Il Ritratto di Mazzini di Luigi Calamatta: una storia curiosa tra scelte estetiche e implicazioni politiche (con una lettera inedita di Giuseppe Mazzini a George Sand) - Dinoia, Rosalba (Incontri. Rivista europea di studi italiani, 2020)
Mazzini’s portrait between aesthetic choices and political implicationsThe intriguing story of Luigi Calamatta's engraving (With an unpublished letter from Giuseppe Mazzini to George Sand)The incident surrounding the Portrait of Mazzini, which the famous Italian engraver and patriot Luigi Calamatta freely interpreted drawing on the painting by Emilie Ashurst Hawkes, Mazzini’s intimate friend, directly inserts itself in the dense relationships that − in the nineteenth century − the emigrated Italian patriots established with the French republican élite in Paris. Two key figures on the political and intellectual scene in Europe, namely the statesman Giuseppe Mazzini and the novelist George Sand, with whom Calamatta confronted himself, were directly involved in the long and controversial process of creating the artwork. This involvement allowed for the Portrait of Mazzini to become an emblematic case in point in the evolution of history of print; initially considered a mere means of reproduction of works by other artists, in the second half of the century the engraving assumed the value of a work of art in itself.